Now, switch! Individuals’ responses to imposed switches between exploration and exploitation - Bidmon, Christina M. (2021)
Individual ambidexterity is an important micro-foundation of organizational ambidexterity. However, switching back-and-forth between exploration and exploitation can be challenging for individuals. Prior research has mostly focused on bottom-up approaches to stimulating individual ambidexterity, yet many organizations are characterized by greater top-down control. Exercising control may complicate the pursuit of individual ambidexterity because it amplifies switching resistance. We draw on an observational study of facilitated strategy workshops to explore the role of switching resistance and steps that can be taken to deal with it in top-down settings. Our findings suggest that imposing switches on individuals tends to trigger a distinct pattern of behavioral responses. Furthermore, we find that increasing control and offering emotional support can reduce switching resistance and help individuals execute ambidextrous work tasks. Our study contributes to the literature on individual ambidexterity by extending it from bottom-up to top-down settings. Specifically, we identify emotional, cognitive and behavioral drivers of switching resistance and unpack the process leading up to resistance. Furthermore, we identify organizational measures relevant for addressing such resistance and resolving ambidexterity at the individual level.